COVID-19 - Havelka, Jacqueline (Philadelphia, Pennsylvania : MASON CREST, 2022)
"The most devastating virus to affect humanity in a century, SARS-CoV-2 went from a curious new disease to a global pandemic within the span of weeks. The global system made it possible for COVID-19 to spread to nearly every country in the world within a month, at which point the virus devastated healthcare systems, paralyzed national economies, and contributed to social unrest and instability. Mask mandates, vaccination, and other issues relevant to the COVID-19 pandemic are explored in this book"--Back cover.
Includes index.
Keywords: COVID-19 (Disease) -- Juvenile literature; Coronavirus infections